Comparing the Functionalities of Quizizz and Wordwall for Interactive Learning - Misfa’atin, Misfa’atin; Daristin, Pipit Ertika; Maisaroh, Ummi (Lembaga Pengembangan Bahasa Universitas Hasyim Asy'ari Tebuireng Jombang, 2024)
The digital era has had a significant impact on various aspects of life, including education. With the advent of electronic learning (e-learning), educational media such as Wordwall and Quizizz have become increasingly popular. Wordwall supports game-based learning with interactive features like Matching Pairs and Random Wheel, which can enhance student engagement. Meanwhile, Quizizz offers an interactive online quiz experience with instant feedback, statistical features, and integration with other learning platforms. Both tools play a significant role in creating engaging and effective learning environments. This study highlights the effectiveness and advantages of each platform in supporting digital-based learning.